2016
DOI: 10.15171/bi.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

The cardiac effects of carbon nanotubes in rat

Abstract: Introduction: Carbon nanotubes (CNTs) are novel candidates in nanotechnology with a variety of increasing applications in medicine and biology. Therefore the investigation of nanomaterials’ biocompatibility can be an important topic. The aim of present study was to investigate the CNTs impact on cardiac heart rate among rats. Methods: Electrocardiogram (ECG) signals were recorded before and after injection of CNTs on a group with six rats. The heart rate variability (HRV) analysis was used for signals analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Depending on the doses of CNTs, some studies showed the persistent pulmonary inflammation 9 14 , transient inflammation 15 17 , and no inflammation 11 , 18 , 19 . It has been confirmed that CNTs can cause the cardiovascular toxicity 20 and increase susceptibility to cardiovascular diseases 21 such as ischemia 22 as well as an increase in the resting heart rate 23 . A very low neurotoxicity of CNTs was observed by Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the doses of CNTs, some studies showed the persistent pulmonary inflammation 9 14 , transient inflammation 15 17 , and no inflammation 11 , 18 , 19 . It has been confirmed that CNTs can cause the cardiovascular toxicity 20 and increase susceptibility to cardiovascular diseases 21 such as ischemia 22 as well as an increase in the resting heart rate 23 . A very low neurotoxicity of CNTs was observed by Chen et al .…”
Section: Introductionmentioning
confidence: 99%
“…CNTs which are used today in the manufacture of cellular scaffolds and tissue engineering as well as in the circulatory system can cause significant toxicity in this organ. Studies showed that CNT increases the heart rate of rats and blocks the potassium channel leading to impaired blood pressure and uncoordinated heartbeat [121].…”
Section: Cntmentioning
confidence: 99%
“…The effects of SWCNTs on keratinocyte cells has been examined; they cause oxidative stress, increase ROSs and cytotoxicity by increasing the accumulation of peroxidation products, free radical production, and loss of macrophages [208,212]. Also, CNTs induce morphological changes in the skin and increase NF-kB [121]; [213], toxicity of these NPs being dosedependent. In a study of the toxicity of SWCNTs, increased (IL)-8 and cytokine expression and decreased cell viability has been reported; toxicity effects on skin cells in in vitro models were reported to be the toxicity of skin fibroblasts [129].…”
Section: Carbon-based Nanostructuresmentioning
confidence: 99%
“…Use of stem cells or biologically compatible, synthetic compounds have been studied extensively, although with greater focus on effects on myocardial contractility and ventricular function rather than arrhythmogenicity. Certain compounds, such as carbon nanotubes, have been studied in a variety of biological approaches, including as a means of potentially enhancing myocardial health (5)(6)(7)(8)(9)(10)(11). One promising aspect of carbon nanotubes is that they are highly conductive.…”
Section: Introductionmentioning
confidence: 99%